Contrasting Common Era climate and hydrology sensitivities from paired lake sediment dinosterol hydrogen isotope records in the South Pacific Convergence Zone. (1st April 2022) - Maloney, Ashley E.; Richey, Julie N.; Nelson, Daniel B.; Hing, Samantha N.; Sear, David A.; Hassall, Jonathan D.; Langdon, Peter G.; Sichrowsky, Ursula; Schabetsberger, Robert; Malau, Atoloto; Meyer, Jean-Yves; Croudace, Ian W.; et al.
Abstract: Hydroclimate on 'Uvea (Wallis et Futuna) is controlled by rainfall associated with the South Pacific Convergence Zone (SPCZ), the southern hemisphere's largest precipitation feature. To extend the short observational precipitation record, the hydrogen isotopic composition of the algal lipid biomarker dinosterol (δ 2 Hdinosterol ) was measured in sediment cores from two volcanic crater lakes on 'Uvea. The modern lakes differ morphologically and chemically but both contain freshwater within the photic zone, support phytoplankton communities inclusive of dinosterol-producing dinoflagellates, and experience identical climate conditions. δ 2 Hdinosterol values track lake water isotope ratios, ultimately controlled in the tropics by precipitation amount and evaporative enrichment. However, in 88-m-deep Lac Lalolalo a steadily decreasing trend in sedimentary δ 2 Hdinosterol values from −227‰ around year 988 CE to modern values as low as −303‰, suggests this lake's evolution from an active volcanic setting to the present system strongly influenced δ 2 Hdinosterol values. Although current hydrology and water isotope systematics may now reflect precipitation and evaporation in this lake, the interaction between these processes and large changes in basin morphology, geochemistry, and hydrology obstruct the recovery of a climate signal from Lac Lalolalo's sedimentary δ 2 Hdinosterol records. This work emphasizes the importance of site replication and the use of complementary climate reconstruction tools, especially when using molecular proxies that may be sensitive to more than one environmental parameter. Contrary to its neighbor, duplicate δ 2 Hdinosterol records from 23-m-deep Lac Lanutavake varied between −277‰ and −297‰ and indicate slightly drier conditions during the time-period known as the Medieval Climate Anomaly (MCA, 950–1250 CE). The δ 2 Hdinosterol signal in Lac Lanutavake was muted compared to published records from 'Upolu (Samoa) and Efate (Vanuatu) indicating that 'Uvea's location is not as sensitive to precipitation variability at sites farther from the SPCZ central axis. Lithogenic runoff proxies combined with δ 2 Hdinosterol support the interpretation of a relatively dry MCA on 'Uvea, 'Upolu, and Efate, potentially due to less intense precipitation, a contracted, or a more zonally oriented SPCZ. Highlights: SPCZ δ 2 Hdinosterol and runoff records indicate a drier Medieval Climate Anomaly. Accurate interpretations of biomarkers require multiproxy and multisite data. Low amplitude precipitation variability over past 2 kyr along central SPCZ axis. Lac Lalolalo δ 2 Hdinosterol records reflect hydrology, not climate.